Proceedings of the 2010 Special Interest Group on Management Information System's 48th Annual Conference on Computer Personnel 2010
DOI: 10.1145/1796900.1796918
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder dissonance

Abstract: When a project perceived to be a failure by one set of stakeholders is perceived as a success by another set of stakeholders we have outcome disagreement. Our objective is to discover if team motivation is affected when developers and managers disagree on a project"s outcome. We also investigate if culture influences team motivation. We collected questionnaire data on 290 completed projects from software engineering practitioners based in Australia, Chile, and USA. We asked if the respondent considered their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Further research should also dive into the effects of culture on team motivation. [22] Furthermore, the suitability of different management styles and SE practices for different cultural indications are a promising field for future studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further research should also dive into the effects of culture on team motivation. [22] Furthermore, the suitability of different management styles and SE practices for different cultural indications are a promising field for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis and findings indicate that for instance cultural differences influence the success of the project [21], [22] and business goals [37]. There are many SE activities identified that are impacted by cultural aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The associated ambiguity, especially as it relates to the fact that 'failure' and 'success' are not notions of contradiction (Baccarini, 1999;Fincham, 2002), makes its definition particularly problematic. The definition of project failure and its associated criteria are heavily dependent on the perceptions of stakeholders (Pereira et al, 2008;Procaccino & Verner, 2002); creating what Verner, Beecham, and Cerpa (2010) refer to as stakeholder dissonance. Traditionally, measures of project failure have been based on generic (Shokri-Ghasabeh & Kavoousi-Chabok, 2009), and quantifiable factors such as time, quality, and cost (Icmeli-Tukel & Rom, 1997), which are time dependent both within and across projects (Pinto & Prescott, 1988;Pinto & Slevin, 1988).…”
Section: Theoretical Driversmentioning
confidence: 99%